PWE-133 Hepatocellular Carcinoma: Impact Of Nice Guidelines On Assessing And Optimising Surveillance. (9th June 2014) - Johnston, E; Khan, R; Ingoe, J; Tritto, G
Abstract : Introduction: Screening for hepatocellular carcinoma (HCC) is only deemed cost-effective in patients at high risk. However, the criteria for identifying patients at risk, particularly in relation to non-cirrhotic hepatitis B, remains ill defined and different international guidelines are not consistent. Recent NICE guidelines proposed offering surveillance to patients with significant fibrosis (≥F2) or age >40 with either high viral load or family history of HCC. The aim of this study was to evaluate how the new NICE guidelines can impact on current practice and on the effectiveness of our surveillance program. Methods: All patients who underwent an abdominal ultrasound for HCC surveillance from 1 st September 2012–31 st August 2013 were identified and the indications evaluated. In a subgroup of these patients with hepatitis B the appropriateness of screening was assessed according to the 2013 NICE guidelines. From the same period, all HCC diagnosed were identified and cross matched with our surveillance list. Results: In the period under study, 1280 surveillance ultrasounds (606 in cirrhosis, 628 in non cirrhotic hepatitis B or C, 46 other) led to 5 diagnoses of HCC. All HCC were found in cirrhotic patients (annual incidence 1.65%). Seventeen further HCC were diagnosed from emergency admissions or referred from elsewhere. One patient had non cirrhotic hepatitis B (78yr old male with a long history of hepatitis B) whilst all the remaining were cirrhotic (2 with hepatitis B). In a randomly selected sample of 200 patients undergoing surveillance ultrasounds, 62% (n = 124) had hepatitis B and 76 had cirrhosis of other aetiology. Of the patients with hepatitis B, an assessment of specific risk factors, particularly level of fibrosis, was not documented in 50 (40%). A further 48 (39%) patients were retrospectively deemed low risk according to NICE guidance. Conclusion: The number of HCC diagnosed through surveillance was low, but still cost effective in cirrhotic patients. The main risk factor for HCC in this cohort was cirrhosis (96.5%). In fact, only 1 non cirrhotic patient with hepatitis B developed HCC and this was on a background of likely advanced fibrosis. None of the HCC from surveillance would have been missed if NICE criteria were used. It is important that patients with chronic hepatitis B all undergo assessment of fibrosis, along with clear documentation of other known risk factors in order to enable better risk stratification. In our experience following NICE guidance to identify high risk patients for surveillance will pick up all cases of HCC and decrease cost by reducing the number of unnecessary ultrasound scans being carried out. Reference: NICE clinical guideline 165 – Hepatitis B (chronic) June 2013 (http://www.nice.org.uk/nicemedia/live/14191/64234/64234.pdf ) Disclosure of Interest: None Declared.